A heuristic modelling for three-dimensional container loading problem. (1st January 2012) - Bandyopadhayay, Asit; Roy, Dilip
In this research paper, we present a heuristic modelling of three-dimensional container loading problem (CLP) developed for a port. It considers the problem of loading containers with non-uniform size and presents a heuristic model. The objective of this work is to develop a computational system to prepare a near optimum container loading plans so that there will be maximum utilisation of container space and hence generation of more revenue. Research works reported in the literature mainly deals with in terms of weight restrictions, which is a simpler version of the problem that can be addressed by using dynamic programming method. Lack of completeness and uniqueness in their optimum solutions has led to the present work. In fact, CLP in terms of volume restrictions is a more interesting but difficult problem. This needs specific attention because sometimes volume is an important consideration than weight under the usual precedence constraints. Here we present a computational system of three-dimensional CLP developed for use in any typical port where, with a given number blocks, one can efficiently arrive at the desired solution.